Jihadism in Europe European youth and the new caliphate - Khosrokhavar, Farhad 1948- (Oxford University Press, 2021)
"European jihadism is a multi-faceted social phenomenon. It is not only linked to the extremist behaviour of a limited group, but also to a broader crisis, including the lack of utopia and loss of meaning among the middle classes, and the humiliation and denial of citizenship among disaffiliated young people in poor districts all over Western Europe. Fundamentally, it is grounded IN AN UNBRIDLED AND MODERN IMAGINATION, IN AN UNEASY RELATIONSHIP WITH SOCIAL, CULTURAL, AND ECONOMIC REALITY. THAT IMAGINATION IS DESCRIBED IN THIS BOOK AMONG YOUNG WOMEN AND THEIR LONGING FOR ANOTHER FAMILY MODEL, ADOLESCENTS AND THEIR DESIRE TO BECOME ADULTS AND TO OVERCOME THE FAMILY CRISIS, PEOPLE WITH MENTAL PROBLEMS FOR WHOM JIHAD WAS A CATHARSIS, YOUNG CONVERTS WHO SOUGHT TO REALIZE THEIR DREAM OF A DIFFERENT RELIGION, IN CONTRAST WITH A DISENCHANTED SECULAR EUROPE. The family and its crisis, in many ways, played a role in promoting jihadism, particularly in families of immigrant origin whose relationship to patriarchy was different from that of the mainstream society in Europe. Among middle class families, the crisis of authority was a key factor for the departure of middle-class youth. At the urban level, a large proportion of jihadists come from poor and ethnically segregated districts with high levels of social deviance and the stigma attached to them. Within these poor districts, a specific subculture was built up (we call it the Slum Culture), which influenced young people and imposed on them a lifestyle likely to combine resentment and deviance with humiliation and denial of citizenship in a difficult relationship with mainstream society. BUT JIHADISM WAS ALSO AN EXPRESSION OF THE LOSS OF HOPE IN THE FUTURE IN A GLOBALIZED WORLD AMONG MIDDLE CLASS AND LOWER-CLASS YOUTH. THE CALIPHATE IN SYRIA PROMISED THE EARTH TO THESE YOUNG PEOPLE DURING ITS ASCENT BETWEEN 2014-2015 AND EVEN AFTER, THIS TIME AS A PROPHET OF A GLOOMY END TIMES"--
Keywords: Islamischer Staat; Fundamentalismus; Djihad; Islam; Europa; Jihad; Muslims / Europe / Attitudes; Islamic fundamentalism / Europe; Muslims / Cultural assimilation / Europe; IS (Organization); Ethnic conflict / Europe; Ethnic conflict; Islamic fundamentalism; Muslims / Attitudes; Muslims / Cultural assimilation; Europe